Comparison of the Effectiveness of Cognitive-Behavioral Interventions in Two Approaches: Coaching and Self-Learning on Marital Satisfaction and Intimacy of Couples - Sedaghat, Negar; Safarinia, Majid; Sadeghi, Elaheh (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to compare the effectiveness of cognitive-behavioral interventions using coaching and self-learning methods on marital satisfaction and couple intimacy.Methods and Materials: This semi-experimental study followed a pre-test–post-test design with a control group and two experimental groups (coaching and self-learning). The statistical population consisted of couples who visited family counseling centers in District 8 of Tehran in 2022 and reported low levels of marital satisfaction and intimacy. A purposive sampling method was used to select 45 participants, who were equally divided into three groups of 15. The coaching group received eight 90-minute cognitive-behavioral sessions, while the self-learning group was given a structured 73-page manual to follow independently over two months. The control group received no intervention. Data were collected using the ENRICH Marital Satisfaction Questionnaire and the Thompson and Walker Marital Intimacy Scale. Analysis of covariance (ANCOVA) and multivariate analysis of covariance (MANCOVA) were used to analyze the results.Findings: ANCOVA results indicated that cognitive-behavioral interventions using the coaching method significantly improved marital satisfaction (η² = 0.30, p < .01) and couple intimacy (η² = 0.372, p < .01), compared to the control group. Similarly, the self-learning method showed significant improvement in marital satisfaction (η² = 0.19, p < .01) and intimacy (η² = 0.23, p < .01), although the effect sizes were smaller.Conclusion: Cognitive-behavioral interventions, particularly through coaching, are effective in enhancing marital satisfaction and intimacy. The presence of a coach facilitates deeper understanding, accountability, and behavioral change, making it a more impactful approach compared to self-directed learning.